PENGARUH IKLAN “INTRODUCTION: JO & JEK” DI YOUTUBE TERHADAP BRAND AWARENESS (Studi Kasus Perusahaan GO-JEK) - Priana, Jordy Revindra; Suwandi, Suwandi (Journal of Entrepreneurship, Management and Industry (JEMI), 2019)
This study aims to analyze the effect of the advertisement “Introduction: Jo & Jek” on YouTube towards brand awareness of GO-JEK as the case study. The independent variable in this study is YouTube advertisement and the dependent variable is brand awareness. The sample used in this study was Universitas Bakrie students who had watched the video advertisement “Introduction: Jo & Jek” from GO-JEK channel on YouTube. The number of sample was 100 people and was collected by non-probability sampling methods and also purposive sampling technique. The analysis method used is simple regression analysis. The result of this study indicated that YouTube advertisement has a positive and significant effect towards brand awareness of GO-JEK customers